Synthesis of Potassium Tetratitanate—Based Molecularly Imprinted Polymer for Selective Adsorption of Dibenzothiophene - Wanzhen Xu; Xudong Zheng; Mengying Gan; Wenjing Zhu; Yunlei Zhang; Yongsheng Yan (Adsorption Science & Technology)
A potassium tetratitanate–based molecularly imprinted polymer (MIP) was prepared by surface molecule–imprinting technique, which involves coating potassium tetratitanate whiskers with silica and modification with 3-methacryloxypropyltrimethoxysilane. The structural properties of the synthesized MIP were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, nitrogen adsorption and scanning electron microscopy. Adsorption behaviour studies were conducted on the prepared MIP, the results of which showed that it has a porous and large surface area. In addition, the prepared MIP showed good adsorptive capacity and selectivity for dibenzothiophene; the adsorption equilibrium time was 180 minutes and the equilibrium adsorption capacity was 20.86 mg/g at 318 K. The adsorptive behaviour followed the Lagergren pseudo-second-order kinetic model and the Freundlich isotherm model. Thermodynamic parameters demonstrated that the adsorption process was spontaneous and endothermic. Thus, based on the study results it can be concluded that the synthesized adsorbent (i.e. MIP) has potential applications for deep desulphurization of gasoline.